Preparation method of high-conductivity and stable sulfide electrolyte and all-solid-state battery
By mixing sulfide electrolytes with ammonium salt, high -conductive and stable sulfide electrolytes with halide covering layers can be generated, and the chemical stability and interface stability of vulcosamide electrolyte are solved. Compatibility improves the performance of all -solid -state batteries.
Patent Information
- Application Number
- CN202411688746.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-01-28
AI Technical Summary
The chemical stability of sulfide electrolytes is poor, and it is prone to structural damage in humid air, resulting in a sharp decline in electrical conductivity and poor interface stability with the electrode. There are serious chemical reactions, catalytic redox and reduction problems, which interfere with the transmission of interface ions/electrons. .
By grinding, suppression and thermal treatment by mixing the electrolytes of the original sulfide with ammonium salts, high -conducting and stable vulcosine electrolytes with halide covering layers are generated. The coating layer of the halogen replaces the sulfur atoms in the electrolytes of sulfide, increases structural confusion, reduces ion migration potential, improves ionic conductivity, and improves the stability of the electrolyte through isolation of water molecules in the air.
Achieve high -chamber temperature ion conductivity, low electronic conductivity, and lithium metal matching with good interface compatibility and air stability. The obtained high -conductive and stable vulcanic electrolyte can effectively suppress the side reaction of the positive interface and the effect of space charge layer effects. , Stop the growth of Zhi crystal and improve the overall performance of the battery.
Smart Images

Figure CN119381537A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium-ion batteries, and in particular to a method for preparing a high-conductivity, stable sulfide electrolyte and an all-solid-state battery. Background Art
[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles and other fields due to their high energy density and high capacity. Traditional lithium-ion batteries use liquid electrolytes, but the flash point of liquid electrolytes is low. Under abnormal conditions such as high current discharge, overcharging, internal short circuit, etc., the electrolyte may heat up and spontaneously combust, or even cause safety problems such as explosion. Solid-state lithium-ion batteries use non-flammable or non-combustible solid electrolytes to replace the flammable organic electrolytes in traditional lithium-ion batteries, which can fundamentally solve the safety problems of lithium-ion batteries. The solid electrolytes used in solid-state lithium-ion batteries have become the focus of research and development in recent years.
[0003] In solid-state battery technology, high-performance solid electrolytes play a vital role and determine the feasibility of fully solid-state batteries. Among many electrolyte systems, sulfide electrolytes have the advantages of easy processing and high ionic conductivity. This combination of characteristics highlights its unique advantages in the development and application of all-solid-state batteries and shows attractive development prospects. However, its chemical stability is poor, and it is very easy to suffer structural damage in humid air, resulting in a sharp drop in conductivity. In particular, the interface stability between sulfide electrolytes and electrodes is poor, and serious chemical reactions and catalytic redox problems on the interface greatly interfere with the transmission of interfacial ions / electrons at the heterogeneous interface, thereby hindering the matching application of electrolytes with oxide positive electrodes and lithium metal negative electrodes.
[0004] CN117497836A uses a liquid phase method to coat an appropriate amount of glass phase type halide electrolyte LiTaCl5M on the surface of argyrodite type electrolyte particles 1 / n, using the good stability of halide electrolytes for high-voltage positive electrode materials to solve the problems of low oxidation potential of sulfide electrolytes and serious side reactions when in direct contact with positive electrode materials. However, the invention has a complex process, it is difficult to accurately control the uniformity of the coating, and there are many variables. In particular, the residual solvent in the liquid phase treatment may have a negative impact on the conductivity of the sulfide electrolyte, and may cause element diffusion to cause changes in the structure of the electrolyte itself, reducing the conductivity; secondly, the coating material involves the precious metal element Ta, which is scarce and difficult to extract and has a high cost; finally, the electrolyte cannot solve the problem of interface failure with the lithium negative electrode, and the high-priced metal is easily reduced by lithium. CN117638268A discloses the application of an ester substance as a surface modifier for sulfide electrolytes. In the process of adding ester homogenate to the sulfide electrolyte, the surface of the sulfide electrolyte is doped with oxygen elements, which changes the soft and sticky characteristics of the sulfide electrolyte surface, avoids the re-agglomeration of sulfide electrolyte particles broken by the rotation speed, thereby reducing the electrolyte particle size, increasing the contact area with the active material, and improving the ion transmission capacity. However, esters dope the electrolyte surface with oxygen, which may have a negative impact on the electrolyte ion conductivity. At the same time, esters, as surface modifiers for sulfide electrolytes, do not effectively inhibit problems such as the interface reaction between electrolytes and active materials (such as oxides) and the space charge layer effect, which is not conducive to achieving high-voltage stability; the use of solvents involved in the treatment process may destroy the electrolyte structure and affect its own high ionic conductivity.
[0005] Based on the above analysis, a preparation method of sulfide electrolyte and an all-solid-state battery that introduces sulfide electrolyte and solves its instability are urgently needed in this industry. Summary of the invention
[0006] In view of the above shortcomings, the purpose of the present invention is to provide a new sulfide solid electrolyte with a halide as a coating layer, which can stably match the unmodified oxide positive electrode and lithium negative electrode, inhibit the positive electrode interface side reaction, space charge layer effect and other problems, and solve the problems of negative electrode interface dendrite growth and electrolyte reduction; by replacing sulfur atoms in the sulfide electrolyte with halogen atoms, the structural disorder is increased and the ion migration barrier is reduced, thereby further improving its own ion conductivity; the halide coating layer isolates water molecules in the air and improves the air stability of the electrolyte. The present invention is achieved by the following technical means:
[0007] The present invention first discloses a method for preparing a high-conductivity, stable sulfide electrolyte, comprising the following steps:
[0008] (1) Under an inert atmosphere, the raw sulfide electrolyte and the ammonium salt are manually ground and then ball-milled to obtain a mixture;
[0009] (2) under an inert atmosphere, pressing the mixture into a sheet-like mixed solid;
[0010] (3) Under an inert atmosphere, the flaky mixed solid is heat treated and ground to obtain the high-conductivity, stable sulfide electrolyte.
[0011] Furthermore, the original sulfide electrolyte in step (1) is selected from: lithium argyrodite type (Li6PS5Cl or Li6PS5Br), lithium germanium phosphorus sulfur type electrolyte (Li 10 GeP2S 12 or Li 10 SiP2S 12 ), glass ceramic electrolyte (Li7P3S 11 or Li3PS4); the ammonium salt is selected from one or more of ammonium chloride, ammonium fluoride, ammonium bromide and ammonium iodide.
[0012] Furthermore, the original sulfide electrolyte is selected from lithium argyrodite type and glass ceramic electrolyte; the ammonia salt is selected from one or more of ammonium chloride, ammonium fluoride and ammonium bromide.
[0013] Further, the original sulfide electrolyte is Li6PS5Cl; the ammonium salt is selected from ammonium chloride and ammonium fluoride;
[0014] Furthermore, in step (1), the ball milling speed is ≥100 rpm / min, and the time is ≥20 min.
[0015] Furthermore, in the mixture of step (2), the molar percentage of the original sulfide electrolyte is 25% to 91%, more preferably 33.3% to 66.7%; the molar percentage of the ammonium salt is 19% to 75%, more preferably 33.3% to 66.7%.
[0016] Furthermore, in step (2), the mixture is pressed at a pressure of 100 to 500 MPa, and a more preferred pressure is 250 to 350 MPa.
[0017] Furthermore, in step (3), the mixed solid heat treatment temperature is 200-600°C, and the more preferred temperature is 250-550°C; the mixed solid heat treatment time is 0.5-6h, and the more preferred time is 1-5h.
[0018] The invention also discloses a high-conductivity and stable sulfide electrolyte prepared according to any one of the above preparation methods.
[0019] The present invention also discloses an all-solid-state battery, which comprises: a positive electrode, a negative electrode and an electrolyte located between the positive electrode and the negative electrode, wherein the electrolyte is the above-mentioned high-conductivity, stable sulfide electrolyte.
[0020] The beneficial effects of the present invention are:
[0021] The invention mixes the original electrolyte with the ammonium salt, grinds it into powder after grinding, pressing and heat treatment, and makes the ammonium salt in the obtained sulfide electrolyte decompose at high temperature to generate hydride gas, which reacts with the original sulfide electrolyte, and the halogen element penetrates into the original sulfide electrolyte lattice. After the halogen element is saturated, it begins to precipitate to form lithium salt, which is evenly wrapped on the surface of the modified sulfide electrolyte. On the one hand, since the ammonium salt contains halogen atoms, the halogen enters the electrolyte lattice, which increases the diversity of the electrolyte's anion sublattice structure and reduces the ion migration barrier, thereby improving its ion transmission capacity, that is, improving the electrolyte ion conductivity; on the other hand, the new lithium salt precipitated by the reaction is wrapped on the surface of the original electrolyte particles to form a coating layer. The low electron conductivity of the lithium salt can effectively prevent electrons from attacking the original sulfide electrolyte, improve the interface stability on the positive electrode side, and because the original sulfide electrolyte is wrapped by the lithium salt, the electron conductivity of the grain boundary is reduced, which is conducive to hindering the growth of dendrites at the lithium negative electrode / electrolyte interface, reducing the strong reduction effect of lithium metal on the sulfide electrolyte, and matching the lithium negative electrode; further, the coating layer is also conducive to isolating water molecules in the air and improving the air stability of the electrolyte. As a result, the obtained high-conductivity, stable sulfide has high room temperature ionic conductivity, low electronic conductivity, good interface compatibility and air stability with lithium metal, so that a high-energy-density all-solid-state battery can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The X-ray diffraction pattern and Rietveld refinement results of the solid electrolyte prepared in Example 1;
[0023] Figure 2 The SEM and element distribution mapping of the solid electrolyte prepared in Example 1;
[0024] Figure 3 This is the EDS quantitative spectrum of the solid electrolyte prepared in Example 1;
[0025] Figure 4 The electrochemical impedance spectrum of the solid electrolyte prepared in Example 1;
[0026] Figure 5 This is a fitting diagram of the polarization current curve of the solid electrolyte prepared in Example 1;
[0027] Figure 6 This is a fitting diagram of the polarization current curve of the solid electrolyte prepared in Comparative Example 1;
[0028] Figure 7 The voltage (current)-time curve of the solid electrolyte assembled lithium symmetric battery prepared in Example 1 during deposition and stripping;
[0029] Figure 8 The maximum voltage and time curve during deposition and stripping of the solid electrolyte assembled lithium symmetric battery prepared in Example 1;
[0030] Fig. 9 Schematic diagram of mapping of the assembled LCO||Li half-cell structure;
[0031] Fig.10 Electrochemical cycling performance of LCO||Li half-cell assembled with solid electrolyte prepared in Example 1;
[0032] Fig.11 Electrochemical cycling performance of LCO||Li-In half-cell assembled with solid electrolyte prepared in Example 1;
[0033] Fig.12 Electrochemical cycling performance of LCO||Li half-cell assembled with solid electrolyte prepared in Comparative Example 1. DETAILED DESCRIPTION
[0034] The specific embodiments of the present invention are described below to facilitate the understanding of the present invention by those skilled in the art, but it should be clear that the present invention is not limited to the scope of the specific embodiments. For those skilled in the art, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the present invention are protected. The experimental methods in the following examples that do not specify specific conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be purchased commercially.
[0035] The first embodiment of the present invention discloses a method for preparing a high-conductivity, stable sulfide electrolyte, comprising:
[0036] mixing a sulfide electrolyte and an ammonia salt to obtain a mixture;
[0037] pressing the mixture into a sheet-like mixed solid;
[0038] The flaky mixed solid is subjected to a heat treatment and then subjected to a second grinding treatment to obtain a sulfide electrolyte;
[0039] Wherein, the above steps are all carried out under an inert atmosphere.
[0040] In this embodiment, the purpose of the mixing is to evenly distribute the original sulfide electrolyte and the ammonia salt. It can be understood that, in order to achieve this purpose, solid phase mixing can be carried out by hand grinding, ball milling, etc.; when the liquid phase method is adopted, low polarity or non-polar solvents such as dichloromethane, n-heptane, p-xylene, trimethylolbenzene, anisole, monochlorobenzene and cyclohexanone are used to dissolve the raw materials, and after sufficient mixing, they are dried to obtain a solid mixture, and then enter the subsequent procedures.
[0041] In order to reduce the number of steps and the risk of introducing impurities in the solvent, the preferred embodiment of the present invention selects solid phase mixing, that is, the original sulfide electrolyte solid and the ammonia salt solid are ground and mixed, and the grinding is preferably ball milling. When ball milling is used, the ball milling speed is ≥100rpm / min and the time is ≥20min.
[0042] Furthermore, the original sulfide electrolyte is selected from lithium argyrodite electrolyte (Li6PS5Cl or Li6PS5Br), lithium germanium phosphorus sulfur electrolyte (Li 10 GeP2S 12 or Li 10 SiP2S 12 ), glass ceramic electrolyte (Li7P3S 11 Or Li3PS4) one or more, the ammonium salt is a halogen ammonium salt.
[0043] It can be understood that in this embodiment, the original sulfide electrolyte is a sulfide electrolyte disclosed in the prior art, preferably the above components, more preferably a lithium sulfide silver germanium ore type, a glass ceramic electrolyte, and most preferably a Li6PS5Cl electrolyte; the ammonium salt is a halogen ammonium salt, that is, an ammonium salt composed of a halogen ion as an anion and an ammonium ion as a cation, and its purpose is to introduce halogen atoms and a precipitated halide coating layer to the sulfide electrolyte during mixing. The presence of halogen atoms can increase the diversity of the anion sublattice structure of the original electrolyte, thereby reducing the ion migration barrier and improving the ion transport capacity, that is, improving the electrolyte ion conductivity, and because the original sulfide electrolyte is wrapped by a halide, it is beneficial to hinder the growth of dendrites at the lithium negative electrode / electrolyte interface, reduce the strong reduction effect of lithium metal on the sulfide electrolyte, and match the lithium negative electrode. The halogen ammonium salt of the present invention is preferably one or more of ammonium chloride, ammonium fluoride, ammonium bromide, and ammonium iodide, more preferably ammonium chloride, ammonium fluoride, and ammonium bromide, and most preferably ammonium chloride and ammonium fluoride.
[0044] Furthermore, in the mixture, the molar percentage of the original sulfide electrolyte is 25% to 91%, and the molar percentage of the ammonia salt is 19% to 75%.
[0045] Preferably, in the mixture, the molar percentage of the original sulfide electrolyte is 33.3% to 66.7%, and the molar percentage of the ammonium salt is 33.3% to 66.7%.
[0046] In this embodiment, the purpose of the above ratio is mainly to coordinate the ratio of the sulfide electrolyte to the precipitated halide coating content. The main ion transmission path of the present invention is through the sulfide electrolyte, and the coating layer lithium halide provides some active lithium ions to enhance the electrolyte ion transmission. If the coating layer ratio increases, the non-lithium ion active medium in the sulfide electrolyte is increased, the ion migration barrier is increased, and it is not conducive to ion conduction; if the coating layer ratio is too small, it cannot play its role in protecting the sulfide electrolyte, and its ability to shield electrons is reduced and its air stability is reduced. Therefore, the present invention uses the above ratio.
[0047] In some specific embodiments, the mixture is pressed at a pressure of 100-500 MPa.
[0048] In some specific embodiments, the mixed solid is heat treated at a temperature of 200 to 600° C. and for a treatment time of 0.5 to 6 hours.
[0049] Example 1
[0050] A method for preparing a high-conductivity, stable sulfide electrolyte comprises the following steps:
[0051] (1) In an argon atmosphere glove box, 2.684 g of Li6PS5Cl argyrodite electrolyte and 0.535 g of NH4Cl ammonium salt were weighed, with molar percentages of 50% and 50%, and manually ground in a mortar for 15 min. The mixture was added to a ball mill and ball milled at a speed of 300 rpm for 30 min to obtain a solid powder mixture;
[0052] (2) In an argon atmosphere glove box, the powder mixture was pressed into a dense disc at a pressure of 300 MPa;
[0053] (3) The disc was calcined at 500°C for 2 h in an argon atmosphere and manually ground into powder after heat treatment to obtain a high-conductivity, stable sulfide solid electrolyte.
[0054] The X-ray diffraction pattern of the high-conductivity, stable sulfide solid electrolyte prepared in this example is shown in Figure 1. Through Rietveld refinement, the contents of the main phase argyrodite electrolyte and the coating layer lithium chloride are 86.6% and 13.4%, respectively, and no other impurity phases are produced, which proves that the high-conductivity, stable sulfide electrolyte is successfully prepared.
[0055] The scanning electron microscope image and element distribution of the high conductivity, stable sulfide solid electrolyte sheet prepared in this example are shown in FIG. Figure 2As shown in the figure, the argyrodite electrolyte particles are 5 to 12 μm. From the mapping, we can see that chlorine is evenly distributed on the surface of the electrolyte particles, while the particles are surrounded by relatively small amounts of sulfur and phosphorus, indicating that the lithium chloride coating layer is generated on the surface of the electrolyte particles. Figure 3 The EDS semi-quantitative analysis showed that the chlorine content on the particle surface was significantly increased.
[0056] Example 2
[0057] A high-conductivity, stable sulfide solid electrolyte was prepared using the same process as in Example 1, except that in step (1), 2.684 g of Li6PS5Cl argyrodite-type electrolyte and 1.07 g of NH4Cl ammonium salt were weighed with molar percentages of 33.3% and 66.7%, and in step (3), the wafer was calcined at 300°C for 3 h in an argon atmosphere.
[0058] Example 3
[0059] A high-conductivity, stable sulfide solid electrolyte was prepared using the same process as in Example 1, except that in step (1), 1.801 g of Li3PS4 glassy electrolyte and 0.268 g of NH4F ammonium salt were weighed with molar percentages of 66.7% and 33.3%, respectively, and in step (3), the wafer was calcined at 400°C for 5 h in an argon atmosphere.
[0060] Example 4
[0061] The same process as in Example 1 was used to prepare a high-conductivity, stable sulfide solid electrolyte, except that in step (1), Li 10 GeP2S 12 5.8876 g of lithium germanium phosphorus sulfur type electrolyte and 0.37 g of NH4F ammonium salt, with molar percentages of 50% and 50%, and in step (3), the wafer is placed in an argon atmosphere and calcined at 400°C for 5 hours.
[0062] Example 5
[0063] A high-conductivity, stable sulfide solid electrolyte was prepared using the same process as in Example 1, except that in step (1), 2.684 g of Li6PS5Cl argyrodite-type electrolyte and 0.979 g of NH4Br ammonium salt were weighed in molar percentages of 50% and 50%, and in step (3), the wafer was calcined at 300°C for 3 h in an argon atmosphere.
[0064] Example 6
[0065] The high-conductivity, stable sulfide solid electrolyte was prepared using the same process as in Example 1, except that in step (3), the wafer was calcined at 500° C. for 1 h in an argon atmosphere.
[0066] Comparative Example 1
[0067] The same process as in Example 1 was used to prepare a high-conductivity, stable sulfide solid electrolyte, except that in step (1), 2.684 g of Li6PS5Cl argyrodite-type electrolyte was weighed, and the molar percentage was 100%.
[0068] Comparative Example 2
[0069] The high-conductivity, stable sulfide solid electrolyte was prepared using the same process as in Example 1, except that in step (3), the wafer was calcined at 800° C. for 2 h in an argon atmosphere.
[0070] Comparative Example 3
[0071] The high-conductivity, stable sulfide solid electrolyte was prepared using the same process as in Example 1, except that 0.535 g of NH4Cl ammonium salt was weighed in step (1), and the molar percentage was 100%.
[0072] Test Example 1
[0073] The impedance of the electrolytes obtained in Examples 1 to 6 and Comparative Examples 1 to 3 was measured using AC impedance technology, and the corresponding ionic conductivity was calculated. The test temperature was 0 to 70°C, the test frequency was 0.01 to 106 Hz, and the test instrument used was Metrohm Autolab (PGSTAT302N). According to the thickness (L) of the electrolyte, the area (S) of the stainless steel sheet, and the impedance (R) of the electrolyte, the ionic conductivity of the electrolyte was calculated using the formula σ=L / (S*R). The EIS of Example 1 is as follows: Figure 4 As shown, the ionic conductivity is calculated to be 11.2 mS cm -1 The test results of all samples are shown in Table 1. It can be seen from the table that the high conductivity and stable electrolyte conductivity of all embodiments are significantly improved compared with the comparative samples. The added ammonium salt has a significant positive effect on the ionic conductivity of the original sulfide electrolyte. The conductivity of the electrolyte not synthesized by the present technical solution is affected by the composition and temperature, and its ion transmission capacity is relatively low.
[0074] Table 1 Ionic conductivity test results
[0075]
[0076]
[0077] Test Example 2
[0078] Polarization current curves were used to measure the electronic conductivity of the novel electrolytes obtained in Example 1 and Comparative Example 1. The polarization voltages were 0.3, 0.4, and 0.5 mV, respectively. The steady-state current density was measured and linear fitting was performed. Figure 5 and Figure 6 As shown, the calculated electronic conductivity of the electrolyte is 1.1×10 -10 S cm -1 and 2.5×10 -8 S cm -1 , the electronic conductivity of the electrolyte is reduced, thanks to the lithium chloride coating layer that isolates the electronic conduction.
[0079] Test Example 3
[0080] The electrolyte obtained in Example 1 was sandwiched between two pieces of lithium metal to construct a Li||Li symmetrical battery. The constant current charge and discharge test was used to evaluate the lithium stability of the electrolyte in the battery. The test instrument used was Land CT2001A, the test temperature was 30°C, and the test results were as follows: Figure 7 As shown in the figure, it can be seen that the Li||Li symmetric battery assembled with the solid electrolyte in Example 1 has a high -2 The deposition and stripping can last for 1500 h without short-circuit failure at a current density of , and the electrolyte and lithium metal have good interface stability.
[0081] Furthermore, the charge and discharge curves of the symmetrical battery at different current densities were tested to determine its critical current density. Figure 8 As shown, it can be seen that the critical current density of the solid electrolyte is 1.75 mA cm -2 , indicating that the electrolyte can be charged and discharged at a larger current.
[0082] Test Example 5
[0083] The electrolytes obtained in Example 1 and Comparative Example 1 were assembled into LCO||Li and LCO||Li-In half-cells in an argon glove box with H2O<0.1ppm and O2<0.1ppm, respectively. The cell mapping structures are as follows: Fig. 9 As shown, the top is the lithium negative electrode, the middle is the electrolyte, and the bottom is the lithium cobalt oxide positive electrode. The charge and discharge test is carried out using Land CT2001A, with a voltage range of 2.5~4.2V and a temperature of 30℃.
[0084] The cycling performance of the obtained LCO||Li and LCO||Li-In half-cells is shown in Table 1. Fig.10 It can be seen from the LCO||Li half-cell that the solid electrolyte obtained in Example 1 has a high -1 ) showed excellent electrochemical performance at a charge and discharge rate of 1.5 % and a discharge capacity of 128.6 mAh g -1 After 2500 cycles, the discharge capacity is 48.9 mAh g -1 , has good electrochemical stability; from Fig.11From the LCO||Li-In half-cell, it can be seen that at a rate of 5C, the battery exhibits excellent cycle stability, with a first-cycle discharge capacity of 89.6 mAh g -1 After 250 cycles, the capacity is 88.4 mAh g -1 . Fig.12 The half-cell assembled with the electrolyte of Comparative Example 1 has almost no capacity when cycled less than 40 times, and its cycle stability is significantly lower than that of Example 1.
[0085] And, a high-conductivity, stable sulfide electrolyte prepared according to the above preparation method. Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit it; although the present invention is described in detail with reference to the above embodiments, a person of ordinary skill in the art should understand that the technical solutions described in the above embodiments can still be modified, or some or all of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solution deviate from the scope of the technical solution of each embodiment of the present invention.
Claims
1. A method for preparing a high-conductivity, stable sulfide electrolyte, comprising: (1) Under an inert atmosphere, the original sulfide electrolyte and the ammonium salt are first manually ground and then ball-milled to obtain a mixture; (2) Under an inert atmosphere, pressing the mixture into a sheet-like mixed solid; (3) Under an inert atmosphere, the flaky mixed solid is heat treated and then ground to obtain a high-conductivity, stable sulfide electrolyte.
2. The preparation method according to claim 1, wherein: The original sulfide electrolyte in step (1) is selected from: Any one of lithium-germanium-sulfur argyro-gemanite electrolyte, lithium-germanium-phosphorus-sulfur electrolyte, and glass-ceramic electrolyte; The ammonium salt is selected from one or more of ammonium chloride, ammonium fluoride, ammonium bromide and ammonium iodide.
3. The preparation method according to claim 2, wherein: The lithium germanium sulfide electrolyte is Li6PS5Cl or Li6PS5Br; the lithium germanium phosphorus sulfur electrolyte is Li 10 GeP2S 12 or Li 10 SiP2S 12 ; The glass ceramic electrolyte is Li7P3S 11 or Li3PS4.
4. The preparation method according to claim 3, wherein: The original sulfide electrolyte is Li6PS5Cl; The ammonium salt is selected from one or more of ammonium chloride and ammonium fluoride.
5. The preparation method according to claim 1, wherein: The ball milling speed in step (1) is ≥100 rpm / min, and the time is ≥20 min.
6. The preparation method according to claim 1, wherein: In the mixture of step (2), the molar percentage of the original sulfide electrolyte is 25% to 91%; the molar percentage of the ammonium salt is 19% to 75%.
7. The preparation method according to claim 1, wherein: The pressing pressure of the mixture in step (2) is 100-500 MPa.
8. The preparation method according to claim 1, wherein: In step (3), the mixed solid heat treatment temperature is 200 to 600° C., and the mixed solid heat treatment time is 0.5 to 6 hours.
9. A high-conductivity, stable sulfide electrolyte prepared according to the preparation method according to any one of claims 1 to 8.
10. An all-solid-state battery, comprising: The high-conductivity, stable sulfide electrolyte as claimed in claim 9, and the positive electrode and the negative electrode.
Citation Information
Patent Citations
Solid electrolyte material and preparation method and application thereof
CN117497836A
Application of ester substance as surface modifier, battery pole piece and preparation method
CN117638268A
High voltage electrolyte
CN102598389A
Sulfide solid electrolyte and preparation method and application thereof
CN113410515A
Sulfide type electrolyte and preparation method and application thereof
CN114243099A
Cited By
Sulfide electrolyte material, solid electrolyte, electrode plate, battery cell or solid-state battery
CN120581683A
Ferroelectric crystal-containing enhanced sulfide electrolyte as well as method and application thereof
CN121484175A